Narratives of aggressive care: Knowledge, time, and responsibility. (June 2014) - Peter, Elizabeth; Mohammed, Shan; Simmonds, Anne
Background: While witnessing and providing aggressive care have been identified as predominant sources of moral distress, little is known about what nurses "know" to be the "right thing to do" in these situations. Research objectives: The purpose of this study was to explore what nurses' moral knowledge is in situations of perceived overly aggressive medical care. Research design: A critical narrative approach was used. Participants: A total of 15 graduate nursing students from various practice areas participated. Findings: Four narrative types were identified, including "Wait and see: medical uncertainty, " "Deflected responsibilities to respond to dying, death, or futility, " "Divergent understandings, responsibilities, and temporalities, " and "Privileged medical understandings and responsibilities." Discussion: The knowledge of differentially situated persons is acknowledged in dissimilar ways, the time required to determine that enough has been done is perceived differently, and how moral responsibilities are understood also varies. Conclusions: A better understanding of how social roles influence how time, knowledge, and responsibility are related to the provision of aggressive care is needed.